MCNP simulations of a glass display used in a mobile phone as an accident dosimeter. (April 2015) - Discher, Michael; Hiller, Mauritius; Woda, Clemens
Abstract: It has been demonstrated that glass display of mobile phones can be used as a device for accident dosimetry. Published studies concentrated on the experimental investigation of parts of the glass display. In the work presented here, the experimental results are compared with results of radiation transport calculations using the Monte Carlo code MCNP5. An experimental setup of an irradiation of an extracted glass display is simulated. The simulation is then extended to a simulation of a modern day mobile phone consisting of all major parts. Simulations are performed for various irradiation conditions and different geometric and material properties. The results of the simulation show a good agreement with the experiments for an extracted glass sample as well as for an actual modern mobile phone. The glass display is exposed to radiation in various angular and energy distributions. Simulated results were compared to experimentally determined results. The effects of the irradiation condition on the photon energy dependence were investigated and variations in the material constants of the display glass composition were discussed. This work affirms the usability of a mobile phone as a versatile and flexible accident radiation detector. Highlights: Simulations of a modern day mobile phone using MCNP are carried out. Results of the simulation show a good agreement with the experiments. Photon energy dependence and angular response for display glass are verified.